Landscape and Fruit Evaluation of Three Privet (Ligustrum sp.) Cultivars in Florida - Julia J. Rycyna; Sandra B. Wilson; Zhanao Deng; Basil V. Iannone; Gary W. Knox (Horticulturae, 2024)
Chinese privet (Ligustrum sinense) has escaped cultivation in 20 states in the USA and is classified as a noxious weed in Florida, where its use is prohibited. There is confusion among producers and consumers surrounding the invasive status of its cultivars. In Florida, cultivars of an invasive wildtype species are also invasive unless proven otherwise and exempted from an invasive ruling. This study evaluated the fruiting and landscape performance of two cultivars of Chinese privet, ‘Variegatum’ (variegated privet) and ‘Sunshine’ (sunshine privet), and an interspecific hybrid of another form of privet, ‘NCLX1’ (L. × vicaryi, Golden Ticket®), planted in southwest, northcentral, and north Florida. ‘Sunshine’ and ‘Variegatum’ privet both performed well throughout the study with average quality ratings ranging from 3.2 to 4.9 (scale of 1–5) and a 100% survival rate during the nearly two-year study. ‘NCLX1’ privet also had a 100% survival rate at the southwest and northcentral sites, but 80% survival at the north Florida site. ‘Variegatum’ privet grew the largest in both height and width compared to ‘Sunshine’ and ‘NCLX1’ privet, that had similar heights. ‘Variegatum’ and ‘NCLX1’ privet flowered during the study, but ‘Sunshine’ privet did not. ‘Variegatum’ privet was the only cultivar evaluated to produce mature fruit and show clear signs of reversion back to its green wildtype form. The DNA content of all three cultivars suggests they are diploids, as is the wildtype form of Chinese privet. These results provide potential alternatives to Chinese privet for use in landscapes but recommend avoiding ‘Variegatum’ privet, due to its frequent reversion to the wildtype and its abundant fruit production.